Point pattern analysis with spatially varying covariate effects, applied to the study of cerebrovascular deaths. (23rd December 2014) - Pinto Junior, Jony Arrais; Gamerman, Dani; Paez, Marina Silva; Fonseca Alves, Regina Helena
<x xml:space="preserve">Abstract</x> This article proposes a modeling approach for handling spatial heterogeneity present in the study of the geographical pattern of deaths due to cerebrovascular disease.The framework involvesa point pattern analysis with components exhibiting spatial variation. Preliminary studies indicate that mortality of this disease and the effect of relevant covariates do not exhibit uniform geographic distribution. Our model extends a previously proposed model in the literature that uses spatial and non‐spatial variables by allowing for spatial variation of the effect of non‐spatial covariates. A number of relative risk indicators are derived by comparing different covariate levels, different geographic locations, or both. The methodology is applied to the study of the geographical death pattern of cerebrovascular deaths in the city of Rio de Janeiro. The results compare well against existing alternatives, including fixed covariate effects. Our model is able to capture and highlight important data information that would not be noticed otherwise, providing information that is required for appropriate health decision‐making. Copyright © 2014 John Wiley & Sons, Ltd.